2009
DOI: 10.1007/s00034-008-9089-9
|View full text |Cite
|
Sign up to set email alerts
|

Selective Filters and Sinusoidal Oscillators Using CFA Transimpedance Pole

Abstract: Using a single current feedback amplifier (CFA) device, two new variable frequency sinusoidal RC oscillators are presented. The transadmittance pole of the device (AD-844) has been utilized in the design for generating sine wave signals covering a range of 1 MHz ≤ f 0 ≤ 31 MHz. Under open-loop conditions, both circuits exhibit resonance characteristics at moderate Q-values (1 ≤ Q ≤ 9). These responses have been experimentally verified with hardware circuit implementation and PSPICE macromodel simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The second order filter uses a single-ended DVCCTA element based lossless inductor L, shunted to C as the Y-admittance in Fig. 1(a); it had been configured with CFAs wherein the devices had been tested a-priori for their nodal relations and parasitic behavior so that the overall filters are built with matched properties [15,22,25]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second order filter uses a single-ended DVCCTA element based lossless inductor L, shunted to C as the Y-admittance in Fig. 1(a); it had been configured with CFAs wherein the devices had been tested a-priori for their nodal relations and parasitic behavior so that the overall filters are built with matched properties [15,22,25]. …”
Section: Resultsmentioning
confidence: 99%
“…At relatively lower frequencies a magnitude error may also be postulated as o % ð1 À j" i jÞ, o % ð1 À j" v jÞ and o % ð1 À j" jÞ albeit these errors are quite low [18,25]. It has been reported that the pole frequencies (!…”
Section: Discussionmentioning
confidence: 99%
“…We next Table I. Details of realizability design examined the effect of the device parasitic capacitances appearing internally at the z-node of CDBA (C z1 ) and at CFA (C z2 ), and also at the y-node (C y ) of the CFA [11,14,15]. Associated with these small capacitors (C z1,2 ∼ 3 pF to 6 pF), there are shunt internal resistances (r y ∼ 3 MΩ and r z ∼ 6 MΩ) which were neglected since we followed the design such that (R/r y,z ) 1.…”
Section: Discussionmentioning
confidence: 99%
“…Recently some such filters using voltage buffers and current amplifiers are reported [3]. With the availability of CDBA [4] and CFA [5,6] type active building blocks, there is renewed interest on analog function circuits using these devices [7,8,9,10,11,12,13,14]. These elements are essentially unity-gain current amplifiers with the provision of additional voltage follower feature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation